First principles calculations of oxygen reduction reaction at fuel cell cathodes - Kotomin, Eugene A.; Mastrikov, Yuri A.; Merkle, Rotraut; Maier, Joachim (Elsevier B.V., 2020)
The efficiency of solid oxide fuel cells (SOFC) depends critically on materials, in particular for the cathode where the oxygen reduction reaction (ORR) occurs. Typically, mixed conducting perovskite ABO3-type materials are used for this purpose. The dominating surface terminations are (001) AO and BO2, with the relative fractions depending on materials composition and ambient conditions. Here, results of recent large-scale first principles (ab initio) calculations for the two alternative polar (La,Sr)O and MnO2 (001) terminations of (La,Sr)MnO3 cathode materials are discussed. The surface oxygen vacancy concentration for the (La,Sr)O termination is more than 5 orders of magnitude smaller compared to MnO2, which leads to drastically decreased estimated ORR rates. Thus, it is predicted for prototypical SOFC cathode materials that the BO2 termination largely determines the ORR kinetics, although with Sr surface segregation (long-term degradation) its fraction of the total surface area decreases, which slows down cathode kinetics.
This study was partly supported by M-ERA-NET project SunToChem (EK, YM). The computer resources were provided by Stuttgart Super-computing Center (Project DEFTD 12939). Authors thank E. Heifets, M. M. Kuklja, M. Arrigoni, D. Morgan, R. Evarestov, and D. Gryaznov for fruitful discussions.
Keywords: Cathode materials; First principles calculations; Fuel cells; Oxygen reduction Reaction (ORR); Perovskites; Polar surfaces; Rate determining step; Research Subject Categories::NATURAL SCIENCES:Physics